Efektifitas Pemanfaatan Media Sosial di Masa Pandemi Covid-19 bagi Pemilik Usaha Kuliner di Kota Surakarta - Annisa Indah Mutiasari; Anggit Dyah Kusumastuti; Destina Paningrum; Rusnandari Retno Cahyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
The study aims to determine the impact of the Covid-19 pandemic and the role of social media as a marketing medium for culinary business owners in the Surakarta Residency. This study uses a qualitative method with a descriptive approach. The sampling method used is the purposive sampling method, with the sample criteria being UMKMs located in the Surakarta Residency that have been marketing through social media.The results show that 62% of respondents still maintain their culinary business. As many as 68% of respondents have a decreased income during the pandemic, and 89% of respondents of culinary businesses have been supported in product marketing by utilizing social media so that they increase in resale.